Czy komputer jest podmiotem poznania? - Hetmański, Marek (Filozofia Nauki, 1996)
The article is devoted the problem of artificial intelligence. The main thesis is that a computer is able to simulate some of human activity, e.g. cognitive activity, but a computer is not substitute for brain (or mind). It can never become an autonomous subject.